Atatürk’ ün yurt gezileri ve bu gezilerin Türk halkına kazandırdıkları - Hayırlıoğlu, Yakup (My University, 1990)
unknown
Keywords: Atatürk, Gazi Mustafa Kemal, T. C. Cumhurbaşkanı 1, 1881-1938_Geziler; Türkiye Cumhuriyeti_Tarih